Sex-Related Microglial Perturbation Is Related to Mitochondrial Changes in a Model of Alzheimer’s Disease - O’Neill, Eoin; Mela, Virginia; Gaban, Aline Sayd; Bechet, Sibylle; McGrath, Aoife; Walsh, Aife; McIntosh, Allison; Lynch, Marina A. (Frontiers in Cellular Neuroscience, 2022)
The critical role of microglia in driving the pathology in Alzheimer’s disease (AD) has been recognized for the past decade or so but the changes that occur which underpin this role remain to be determined. One contributory factor is the enhanced production of inflammatory mediators and it is now known that microglia with this secretory phenotype exhibit other adaptations including in their morphology, function and metabolism. AD, like many neurological disorders, demonstrates a sex bias and recent evidence indicates that the sexual dimorphism in microglial function, which has been recognized for many years in early development, persists into adulthood and ageing. Here, we demonstrate sex-related differences in microglia from post mortem tissue of male and female AD patients and a marked increase in the number of dystrophic and rod-shaped microglia in tissue from female AD patients compared with males. Furthermore, there was an increase in iron-laden microglia in tissue from female AD patients and this has been reported to reflect mitochondrial changes. To address this further, we assessed changes in microglia from male and female APP/PS1 mice and demonstrate that iron accumulation in microglia is increased to a greater extent in tissue prepared from females compared with males. This was associated with enhanced inflammation and expression of genes coding for proteins that modulate mitochondrial function. The findings suggest that sex-related differences in the severity and perhaps incidence of AD may, at least in part, arise from sexual dimorphism in microglia.